World War I and the birth of American intelligence culture. Issue 3 (16th April 2017) - Stout, Mark
Abstract: Historians and practitioners generally date the origins of modern American intelligence to the Office of Strategic Services (1942–1945) and the National Security Act of 1947 which created the CIA and the U.S. Intelligence Community. These claims are CIA-centric and focus on interagency structures. However, modern American intelligence actually has deeper roots of a cultural nature. An observable American intelligence culture was in place by the end of World War I. Not all the aspects of this culture were unique to the United States and, of course, cultures change over time. However, all of the components of early American intelligence culture discussed here are observable in today's Intelligence Community.